A tug-of-war in intraductal papillary mucinous neoplasms management: Comparison between 2017 International and 2018 European guidelines. Issue 8 (August 2021) - Crippa, Stefano; Fogliati, Alessandro; Valente, Roberto; Sadr-Azodi, Omid; Arnelo, Urban; Capurso, Gabriele; Halimi, Asif; Partelli, Stefano; Ateeb, Zeeshan; Arcidiacono, Paolo Giorgio; Lohr, J. Matthias; Falconi, Massimo; et al.
Abstract: Background: 2017 International and 2018 European guidelines are the most recent guidelines for intraductal papillary mucinous neoplasms management. Aim: to evaluate the diagnostic accuracy of these guidelines in identifying malignant IPMN. Methods: data from resected patients with IPMN were collected in two referral centers. Features of risk associated to cancerous degeneration described in International and European guidelines were retrospectively applied. Sensitivity, specificity, positive and negative predictive value in detecting malignant disease were calculated. Results: the study includes 627 resected patients. European guidelines suggest resection in any patient with at least one feature of moderate-risk. International guidelines suggest that patients with moderate-risk features undergo endoscopic ultrasound before surgery. European guidelines had a higher sensitivity (99.2% vs. 83%) but a lower positive predictive value (59.5% vs. 65.8%) and Specificity (2% vs. 37.5%). European guidelines detected almost all malignancies, but 40% of resected patients had low-grade dysplasia. 297 patients underwent endoscopic ultrasound before surgery. 31/116 (26.7%) tumors radiologically classified as "worrisome features" were reclassified as "high-risk stigmata" by endoscopic ultrasound and 24/31 were malignant IPMN. Conclusions: European and International guidelines have a relatively low diagnostic accuracy, being European guidelines more aggressive. Endoscopic ultrasound can improve guidelines accuracy in patients with moderate-risk features.